Increasing carbohydrate availability in the hindgut promotes hypothalamic neurotransmitter synthesis: aromatic amino acids linking the microbiota–brain axis. Issue 5 (15th May 2019) - Gao, Kan; Pi, Yu; Mu, Chun‐Long; Farzi, Aitak; Liu, Zhuang; Zhu, Wei‐Yun
Abstract: The gut microbiota is increasingly recognized to modulate brain function by recent studies demonstrating the central effects of various gut microbial manipulation strategies. Our previous study demonstrated that antibiotic‐induced alterations of hindgut microbiota are associated with changes in aromatic amino acid (AAA) metabolism and hypothalamic neurochemistry, while the underlying mechanistic insight is limited. Given that the microbial AAA metabolism can be affected by luminal carbohydrate availability, here we hypothesize that increasing hindgut carbohydrate availability affects the expression of neurotransmitters in the porcine hypothalamus. A hindgut microbiota‐targeted strategy was adopted by increasing hindgut carbohydrate availability in a cecal‐cannulated piglet model. Mechanistic involvement of AAAs along the gut microbiota−brain axis was further investigated in mice and neuronal cells. Increasing carbohydrate availability by cecal starch infusion led to a decrease in hindgut AAA metabolism, and an increase in systemic AAA availability, central AAA‐derived neurotransmitters (5‐HT, dopamine), and neurotrophin BDNF in piglets, indicating that hindgut microbiota affect hypothalamic neurochemistry in an AAA‐dependent manner. Single AAA i.p . injection in mice revealed that an increase in circulating tryptophan and tyrosine elevated their concentrations in brain and finally promoted the expressions of 5‐HT, dopamine, and BDNF in a time‐dependent manner. Neuronal cells treated with single AAAs in vitro further demonstrated that tryptophan and tyrosine enhanced 5‐HT and dopamine synthesis, respectively, and promoted BDNF expression partly through the 5‐HT1A/DRD1‐CREB pathway. Our study reveals that increasing hindgut carbohydrate availability promotes hypothalamic neurotransmitter synthesis and that AAAs act as potential mediators between hindgut microbiota and brain neurochemistry. Abstract : The gut microbiota is increasingly recognized to modulate brain function. We proposed a model of the impact of changes in microbial composition and metabolism in large intestine on central neurochemistry. Our findings indicate that aromatic amino acids are potential mediators along the large intestinal microbiota–brain axis.